2007
DOI: 10.1139/f07-070
|View full text |Cite
|
Sign up to set email alerts
|

Population genetic structure in the North Atlantic Greenland halibut (Reinhardtius hippoglossoides): influenced by oceanic current systems?

Abstract: We report statistically significant genetic structure among samples of Greenland halibut (Reinhardtius hippoglossoides), rejecting the null hypothesis of panmixia in the North Atlantic. The species appears instead to be subdivided into partially isolated populations, with some evidence for isolation by distance. However, there is a dichotomy between transatlantic sample comparisons and those within a regional current system, even when geographic distance is similar. Calculating geographic distance along the fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
53
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(59 citation statements)
references
References 37 publications
5
53
1
Order By: Relevance
“…Greenland halibut is highly migratory, the migrations are partly size selective and occur to un-fished areas and the stock boundaries in the region are not completely known (Godø and Haug 1989;Albert 2003;Knutsen et al 2007;Albert and Vollen 2015). Although the present study did not find any difference in growth rate between recaptures from different management areas, a basin-wide study of growth and migration is required to establish a fully representative picture of the variability in growth within the population.…”
Section: Growth Estimatesmentioning
confidence: 99%
“…Greenland halibut is highly migratory, the migrations are partly size selective and occur to un-fished areas and the stock boundaries in the region are not completely known (Godø and Haug 1989;Albert 2003;Knutsen et al 2007;Albert and Vollen 2015). Although the present study did not find any difference in growth rate between recaptures from different management areas, a basin-wide study of growth and migration is required to establish a fully representative picture of the variability in growth within the population.…”
Section: Growth Estimatesmentioning
confidence: 99%
“…The erosion of subpopulations could explain why some divisions in our analysis fell below the 1:1 line of expected habitat productivity. Knutsen et al (2007) observed genetic subpopulation structure among Greenland halibut (Reinhardtius hippoglossoides) and that differentiation increased with distance. They theorized that 2 genetically different populations exist and that ocean currents play a major role in determining population structure (during larval stages).…”
mentioning
confidence: 90%
“…They theorized that 2 genetically different populations exist and that ocean currents play a major role in determining population structure (during larval stages). Notably, for this species, dissimilarity between management units and stock structure was identified by genetic analysis (Knutsen et al, 2007). If subpopulations exist, assessing distinct stocks as a single large stock often runs the risk of overestimating stock size; such a practice was likely responsible for the collapse of the stock of Atlantic cod (Gadus morhua) (e.g., Sterner, 2007).…”
mentioning
confidence: 99%
“…It is also possible that population decline and isolation by distance will have generated geographic patterns of genetic differentiation in this species. When dispersion is primarily driven by larval drift, an isolation by distance pattern could be expected, either by geographic distance or along current paths (for example, Knutsen et al, 2007). In this paper, we used 13 microsatellite loci to test the hypothesis that the proposed single dominant spawning site and subsequent gradual migration, or some level of periodic re-distribution during reproduction (necessary if adult fish remain geographically segregated by sex at other times) has led to genetic panmixia across an extended geographic range.…”
Section: Introductionmentioning
confidence: 99%